COMPARATIVE EVALUATION OF THE In Vitro ANTIMICROBIAL AND ANTIOXIDANT POTENTIAL OF Telfairia occidentalis SEED ESSENTIAL OIL AND CRUDE EXTRACT - Osinubi, Adejoke Deborah; Njoku, Isaac Saint; Abdullahi, Azeez Opeyemi; Semire, Olubusayo Funmilola; Sangosanya, Ademola Emmanuel (FUDMA Journal of Sciences, 2026)
Antimicrobial resistance is a prevalent health challenge affecting human, animal, and environmental health, while oxidative stress contributes to an increased susceptibility of humans to infections due to an increased free radical activity, thus requiring urgent alternative solutions. The present work, therefore, compares the therapeutic potential of the crude extract (CE) and essential oil (EO) of Telfaria occidentalis seed. Oil extraction was achieved by steam distillation, and crude extract by maceration. GC-MS analysis revealed the chemical composition of the oil. Agar-well diffusion was used for bioassay screening, while FRAP, DPPH and NO scavenging were used for antioxidant activity. Antimicrobial evaluation against five bacterial strains demonstrated that the CE exhibited stronger antimicrobial activity than the oil, with inhibition zones (IZ) (mm) of 20.00±1.11: K. pneumonia, 21.00±1.26: E. coli, 18.00±1.23: S. aureus, 23.00±1.02 P. aeruginosa, and 24.00±1.24: S. typhi, while the essential oil had IZ of 17.00±1.24, 16.00±1.16, 12.00±1.11, 18.00±1.12, and 15.00±1.32 against K. pneumoniae, E. coli, S. aureus, P. aeruginosa, and S. typhi, respectively. However, the EO demonstrated superior NO scavenging (IC50: CE: 28.32 % vs EO: 30.25), DPPH scavenging (EO: 62.22 μg/mL vs. CE: 66.22 μg/mL) and FRAP activities (EO: 3.42 μg/mL vs CE: 2.10 μg/mL) than the CE. These findings indicate that the CE has better antimicrobial potential than the volatile oils, while the oil displayed better antioxidant activity across all assays employed.  To conclude, the crude extract showed promise as a potential source of lead compounds for developing treatments against multidrug-resistant pathogens. In addition, the strong antioxidant activity of...
Keywords: Telfairia occidentalis; Antimicrobial; Antioxidant; GC-MS; Crude extract; Essential oil